THE CONTENT OF CONTEMPORARY READERS IN THE CONTEXT BY BREEDING THE SENSE OF RESPONSIBILITY - Sviontyk, Olexandra (Mountain School of Ukrainian Carpaty, 2018)
The article deals with the content filling of modern readers for children of junior school age in solving the problem of raising the sense of responsibility, developing social behavior and cultural views as manifestations of moral values. The author of the article gives a critical assessment of the social conditions of the insufficient attention of the educational community to the problem of forming a sense of responsibility as one of the socially important features of the person's character. Emphasizes the necessity of developing a strategy for modern education, which through readers promotes the updating of the above-mentioned educational problem. Taking the attention to the school of the first degree, as the basis for the development of the moral principles of the child, the conscious use of social norms of behavior, manifestations of emotional sensitivity to the environment, the author emphasizes the importance of the consistent influence of the collection of texts of educational works, draws attention to the need for systematic conduct of moral and ethical conversations with a pedagogue with children about the contents of the read. Such means encourage students to actively think and practice, develop a responsible attitude towards their own lives, understand the importance of their educational responsibilities during school education, and develop a child's world outlook and its significance in socially useful activities. The purpose of the article is to outline the advantages of using the educational texts of readers in the formation of moral virtues, in particular, responsibility as one of the important qualities of a modern person, which must acquire moral virtues for the further development of our state. The content of readers of recent years, which presents teachers and parents the possibility of education of children of morality as a means of educational literature as the main one in the formation of worldview, is highlighted. In the analysis of texts attention to developmental exercises, linguistic problems, the use of additional means in the interest of children with a textbook.